Discount rates, debt maturity, and the fiscal theory - Alexandre Corhay; Thilo Kind; Howard Kung; Gonzalo Morales (Leibniz Institute for Financial Research SAFE, 2021)
This paper examines how the transmission of government portfolio risk arising from maturity operations depends on the stance of monetary/fiscal policy. Accounting for risk premia in the fiscal theory allows the government portfolio to affect the expected inflation, even in a frictionless economy. The effects of maturity rebalancing on expected inflation in the fiscal theory directly depend on the conditional nominal term premium, giving rise to an optimal debt maturity policy that is state dependent. In a calibrated macro-finance model, we demonstrate that maturity operations have sizable effects on expected inflation and output through our novel risk transmission mechanism.
urn:nbn:de:hebis:30:3-616375
Keywords: 330; Term structure of interest rates; Fiscal theory of the price level; Bond risk premia; Government debt; DSGE models; Nonlinear solution methods